How labor market institutions influence the relationship between exchange rate regimes and economic growth - Vytautas Kuokštis; Muhammad Asali; Simonas Algirdas Spurga (PLoS ONE, 2025)
How do exchange rate regimes affect economic growth? Although this topic has attracted considerable empirical attention, a definitive answer remains elusive. This study aims to advance our understanding by examining how labor market flexibility affects the link between exchange rate regimes and growth. Using a panel of 194 countries from 1970 to 2019, we find that in developing economies, fixed exchange rate regimes hinder growth when labor markets are highly rigid but boost growth when labor markets are highly flexible. We also demonstrate that this relationship varies depending on which labor market flexibility indicator is used, reflecting the differences in each measure’s geographic and temporal coverage.